2006
DOI: 10.1016/j.geomorph.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian shear stress ratio measurements within mesquite-dominated landscapes of the Chihuahuan Desert, New Mexico, USA

Abstract: A field study was conducted to ascertain the amount of protection that mesquite-dominated communities provide to the surface from wind erosion. The dynamics of the locally accelerated evolution of a mesquite/coppice dune landscape and the undetermined spatial dependence of potential erosion by wind from a shear stress partition model were investigated. Sediment transport and dust emission processes are governed by the amount of protection that can be provided by roughness elements. Although shear stress partit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 41 publications
3
64
0
Order By: Relevance
“…Dupont et al [52] coupled a LES model with a physically based saltation model to resolve turbulent wind flow over heterogeneous vegetated landscapes composed of trees and shrubs. The erosion patterns simulated by Dupont et al's [52] model were qualitatively consistent with previous wind tunnel [59,78] and field [46,140] observations. Minimal dune models (e.g., [168,169]), which combine analytical descriptions of turbulent wind velocity with continuum saltation models, have also been used to successfully simulate transitions between barchan and parabolic dunes [169,170].…”
Section: Computational Fluid Dynamics (Cfd) Modellingsupporting
confidence: 85%
See 1 more Smart Citation
“…Dupont et al [52] coupled a LES model with a physically based saltation model to resolve turbulent wind flow over heterogeneous vegetated landscapes composed of trees and shrubs. The erosion patterns simulated by Dupont et al's [52] model were qualitatively consistent with previous wind tunnel [59,78] and field [46,140] observations. Minimal dune models (e.g., [168,169]), which combine analytical descriptions of turbulent wind velocity with continuum saltation models, have also been used to successfully simulate transitions between barchan and parabolic dunes [169,170].…”
Section: Computational Fluid Dynamics (Cfd) Modellingsupporting
confidence: 85%
“…During the 1990s, more attention was given to the development of drag partitioning techniques that could establish the wind momentum flux at the soil surface in the presence of roughness elements. The schemes of Raupach [57,121] and Marticorena and Bergametti [118] were widely adopted on the basis of their good agreement with wind tunnel experiments using solid objects on non-complex surfaces (e.g., [51,71,[140][141][142][143]). However, the drag partition schemes have also been found to be limited in application in several respects.…”
Section: Drag Partition Schemesmentioning
confidence: 99%
“…Brown et al (2008) found no significant effect of different spatial arrangements of non-erodible roughness elements on the drag partition. (ii) Field experiments with no control over the wind conditions (Musick and Gillette 1990;Wolfe and Nickling 1996;Wyatt and Nickling 1997;Lancaster and Baas 1998;King et al 2006;Gillies et al 2007). In field experiments it is difficult to decouple the influences of the plants on surface shear stress from those induced by the variations in the wind.…”
Section: Introductionmentioning
confidence: 99%
“…Gillies et al (2007) found that the Raupach (1992) drag partition model performed very well for regular arrays of solid elements of different roughness densities within a large open area. (iii) Spatial and temporal averages: only limited data are available on local peak shearstress values (Crawley and Nickling 2003;King et al 2006;Brown et al 2008) or temporal variations of surface shear stress (Sutton and McKenna-Neumann 2008). Sutton and McKenna-Neumann (2008) examined bed level flow patterns around solid cylinders for varying roughness densities and correlated vortices shed by the obstacles with their erosive capability.…”
Section: Introductionmentioning
confidence: 99%
“…The method used in Raupach (1992 19 20 To test the theory of Raupach (1992) The simplicity of Eq. (7) is a strength for its application, in that it requires only a few measurable 2 parameters (Wolfe and Nickling, 1996; Lancaster and Baas, 1998; King et al, 2006). This 3 approach is widely used today in wind erosion models.…”
mentioning
confidence: 99%